The Prognostic Value of Sarcopenia in Acute Myeloid Leukemia Patients and the Development and Validation of a Novel Nomogram for Predicting Survival - Sun, Qian; Cui, Jialin; Liu, Wenjie; Li, Jianyong; Hong, Ming; Qian, Sixuan (Frontiers in Oncology, 2022)
Background: Acute myeloid leukemia (AML) occurs frequently in the elderly, of whom the prognosis is dismal. Sarcopenia is a progressive and generalized skeletal muscle disorder associated with an increased possibility of adverse outcomes. This study aims to explore the prognostic value of sarcopenia in AML patients and develop a novel prognostic model. Methods: A total of 227 AML patients were enrolled. Body composition was assessed by bioelectrical impedance analysis before treatment. Sarcopenia was diagnosed by low muscle quantity. Cox proportional hazard regression model were applied to verify prognostic variables for overall survival (OS) and disease-free survival (DFS). A novel prognostic model of nomogram was developed and validated by ‘R’. Results: Forty-one (18.1%) patients were defined as sarcopenia. The median age of the sarcopenic group was significantly greater than the non-sarcopenic group (median 70 vs. 64 years, P = 0.001). Sarcopenic patients showed significantly less height (P = 0.002), weight (P <0.001), Body Mass Index (P <0.001), Fat Mass (P = 0.017), Fat-free Mass (P <0.001), Appendicular Skeletal Muscle Mass (P <0.001), Skeletal Muscle Index (P <0.001), Fat-free Mass Index (P <0.001), and hemoglobin level (P = 0.025) than the non-sarcopenic ones. Patients in the sarcopenic group also showed a statistically shorter OS and DFS (median OS: 13.7 vs. 55.6 months, P = 0.003; median DFS: 12.5 months vs. not reached, P = 0.026). ELN high risk [Hazard Ratio (HR): 1.904, 95% Confidence Interval (CI): 1.018–3.562, P = 0.044), sarcopenia (HR: 1.887, 95% CI: 1.071–3.324, P = 0.028), and reduced-intensity regimens (HR: 3.765, 95% CI: 1.092–12.980, P = 0.036) were independent predictors for OS in multivariate analysis. A nomogram for predicting OS was constructed using the above three factors. The c index, calibration plots and decision curve analyses (DCA) showed better discrimination, calibration, and net benefits of the nomogram than the ELN model. Conclusion: Sarcopenia was common and had an inferior prognosis in AML and needs more attention in clinical practice.